Implementasi Metode Demonstrasi Kontekstual dalam Menguatkan Pemahaman Praktis Siswa pada Materi Pengurusan Jenazah: Implementing Contextual Demonstration Method for Enhancing Students’ Practical Understanding of Funeral Management - Ibnu Hakim; Imam Suhadi (Madrasah Tsanawiyah DDI Cilellang, 2025)
The teaching of fiqh related to funeral management remains predominantly theoretical, resulting in students’ limited practical competence. This study aims to analyze the implementation of a contextual demonstration method in teaching funeral management, along with its challenges and solutions. Employing a qualitative descriptive approach, the study involved purposively selected teachers and students as informants. Data were gathered through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. Data validity was ensured through source and technique triangulation. The findings indicate that the contextual demonstration method effectively enhances students’ conceptual understanding and practical skills through three phases: pre-demonstration, practice, and feedback. Challenges such as varying student abilities, large class sizes, and limited instructional time were addressed through adaptive strategies, including small group work, video-based learning, modified practice materials, and remedial sessions. This study underscores the critical role of teachers as adaptive facilitators and highlights the importance of integrating contextual demonstration with differentiated instruction and pedagogical innovation as key to effective practice-based fiqh education. However, the study is limited to a single school with a small sample size, limited practice facilities, and short instructional time, thus restricting the generalizability of the findings. The qualitative approach prioritizes contextual understanding over comparative data, and therefore, the method’s effectiveness could not be statistically measured.